Culture and society in medieval Galicia
1 online resource.
Keywords: In Culture and Society in Medieval Galicia , twenty-three international authors examine Galicia’s changing place in Iberia, Europe, and the Mediterranean and Atlantic worlds from late antiquity through the thirteenth century. With articles on art and architecture; religion and the church; law and society; politics and historiography; language and literature; and learning and textual culture, the authors introduce medieval Galicia and current research on the region to medievalists, Hispanists, and students of regional culture and society. The cult of St. James, Santiago Cathedral, and the pilgrimage to Compostela are highlighted and contextualized to show how Galicia’s remoteness became the basis for a paradoxical centrality in medieval art, culture, and religion. Contributors are Jeffrey A. Bowman, Manuel Castiñeiras, James D'Emilio, Thomas Deswarte, Pablo C. Díaz, Emma Falque, Amélia P. Hutchinson, Amancio Isla, Henrik Karge, Melissa R. Katz, Michael Kulikowski, Fernando López Sánchez, Luis R. Menéndez Bueyes, William D. Paden, Francisco Javier Pérez Rodríguez, Ermelindo Portela, Rocío Sánchez Ameijeiras, Adeline Rucquoi, Ana Suárez González, Purificación Ubric, Ramón Villares, John Williams †, and Roger Wright.